Recovery of Digital Assets and Cryptocurrencies in Civil Enforcement Proceedings: Key Challenges - Pranevičienė, Kristina; Sadzevičius, Martynas; Gaubienė, Neringa (PRAWO i WIĘŹ, 2025)
This paper addresses the challenges of recovering digital assets (particularly cryptocurrencies) in civil enforcement proceedings, highlighting the unique legal issues raised by their intangible and decentralised nature. Traditional legal norms designed for tangible assets often fail to address these complexities, leading to difficulties in enforcing judgments involving digital assets. The paper examines the evolving legal landscape, including recent case law that examines the status of digital assets as objects of property rights. It also identifies key legal gaps and proposes solutions to ensure efficient enforcement procedures, with a particular focus on the recovery of cryptocurrencies. The study draws on comparative legal analysis and emerging regulatory trends to provide a comprehensive overview of potential reforms needed to adapt to the digital asset environment.